2019
DOI: 10.1186/s12870-019-2073-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis identifies genes related to the waxy coating on blueberry fruit in two northern-adapted rabbiteye breeding populations

Abstract: BackgroundBlueberry is of high economic value. Most blueberry varieties selected for the fresh market have an appealing light blue coating or “bloom” on the fruit due to the presence of a visible heavy epicuticular wax layer. This waxy layer also serves as natural defense against fruit desiccation and deterioration.ResultsIn this study, we attempted to identify gene(s) whose expression is related to the protective waxy coating on blueberry fruit utilizing two unique germplasm populations that segregate for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Interestingly, Scar exhibited weak negative correlations with Weight and Dia, and a weak positive correlation with 3 mm. 1 Correlation coefficients in bold are significantly different from zero at the p level shown in the following row. 2 NS, not significant (p > 0.05).…”
Section: Fruit Quality Traitsmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, Scar exhibited weak negative correlations with Weight and Dia, and a weak positive correlation with 3 mm. 1 Correlation coefficients in bold are significantly different from zero at the p level shown in the following row. 2 NS, not significant (p > 0.05).…”
Section: Fruit Quality Traitsmentioning
confidence: 94%
“…The popularity of blueberry has risen dramatically in recent years. Production in the United States, the largest producer of blueberries, has more than doubled from 2005 to 2015 (United States Department of Agriculture-National Agricultural Statistics Service (USDA-NASS)) and has increased worldwide by 58% from 2009 to 2014 (United Nations Food and Agriculture Organization) [1]. Blueberry consumption has increased as well, by approximately 3-fold from 2000 to 2010 in the U.S., likely due to greater awareness of its high anthocyanin content and its many health benefits [2].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, we reported the first next-generation sequencing transcriptome (from 454 sequencing) of the species [19]. More recently, in 2019, we published a transcriptome from an RNA-seq analysis aimed at identifying gene(s) important for wax accumulation on blueberry fruit [44,45]. We also examined the expression levels of the structural genes of the anthocyanin biosynthesis pathway in treated fruits (35S:MYB) and compared them with those from fruits infiltrated with an empty vector (35S) and untreated mutant fruits (control).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, we reported the first next-generation sequencing transcriptome (from 454 sequencing) of the species [19]. More recently, in 2019, we published a transcriptome from an RNA-seq analysis aimed at identifying gene(s) important for wax accumulation on blueberry fruit [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Due to global climate change effects, further research involving comprehensive phenotypic, molecular, and genetic characterization of the impact of heat stress on blueberries has become essential. Comparative transcriptome analyses performed in the past few years have revealed molecular and genetic components of several traits, including fruit and color development [ 14 ], flowering pathways [ 15 ], fruit ripening and biosynthesis of bioactive compounds [ 16 ], waxy coating on fruit [ 17 ], anthocyanin synthesis [ 18 ], and cold acclimation pathways [ 19 ] in blueberry. However, no studies have reported the transcriptome analysis of blueberry plants under high-temperature stress.…”
Section: Introductionmentioning
confidence: 99%